2018
DOI: 10.14196/mjiri.32.9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high-dose oral erythromycin on feeding intolerance in preterm neonates: A randomized controlled trial

Abstract: There are conflicting results regarding the use of prophylactic or rescue administration of different doses of oral erythromycin in preterm infants. →What this article adds: This study aimed at assessing the effects of 40 mg/kg/day oral erythromycin on feeding intolerance in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Thus, tele-nursing has been able to promote health behaviors [35]. Kawaguchi et al (2004) found that the telenursing system helps chronic patients to have better self-care, which may be due to regular follow-up and reminders of patients through telenursing, continuous patient education, emphasis on regular use of drugs, mentioning the side effects of the disease in telephone calls to patients and also controlling patients' weight [36]. Williams et al (2012) investigated the impact of tele-nursing in special wards and found that tele-nursing reduced costs, increased patient safety, and improved health care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, tele-nursing has been able to promote health behaviors [35]. Kawaguchi et al (2004) found that the telenursing system helps chronic patients to have better self-care, which may be due to regular follow-up and reminders of patients through telenursing, continuous patient education, emphasis on regular use of drugs, mentioning the side effects of the disease in telephone calls to patients and also controlling patients' weight [36]. Williams et al (2012) investigated the impact of tele-nursing in special wards and found that tele-nursing reduced costs, increased patient safety, and improved health care.…”
Section: Resultsmentioning
confidence: 99%
“…Tele-nursing is more accessible and efficient for patients and guides the caller to the right path to reach the desired level of health and self-care (Figure 2) [32][33][34][35]. Tele-nursing reduces referral to emergency departments and increases productivity in nursing procedures [36][37][38]. In many cases, after discharge from the hospital, the patient is primarily responsible for self-care at home [39].…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies had a total score between 5-9/14 (moderate risk of bias), this score indicates the moderate quality of the studies. Twelve studies had a total score between 10-14/14 (low risk of bias), this score indicates the high quality of the studies [32][33][34][35]. 3 and Table 4) [36][37][38].…”
Section: Bias Assessmentmentioning
confidence: 99%
“…Today, with the introduction of beta 2 agonists, theophylline and aminophylline are used only in cases of severe asthma [35].…”
Section: Phosphodiesterase Inhibitors (Pde-i)mentioning
confidence: 99%